Use-wear analysis of grinding tools and the exploration of plant processing in the Neolithic of Europe: State of the art and perspectives. (June 2022) - Hamon, Caroline
Highlights: Different techniques and grinding systems were employed during the Neolithic in Europe. A large spectrum of plants was processed, including cereals, legumes, nuts and grasses. Important experiment referentials have been compiled in order to help refine our interpretation. Methods of use-wear analysis include qualitative and quantitative observations. Phytolith and starch grain analysis offer complementary results. Abstract: Grinding and pounding implements are among the most widespread and most informative artefacts when it comes to addressing questions related to plant exploitation, especially in the field of food preparation practices. While use-wear analysis using optical microscopy (stereomicroscope and metallographic microscope, quantification using rugosimetry, confocal microscopy and 3D analysis combined with GIS modelling) and microresidues analysis (phytoliths, starch grains, palynomorphs) were considered innovative fields of research at the start of the 2000′s, they are now routinely and effectively applied in combination. Functional analysis of grinding tools from Late Mesolithic and Neolithic contexts in Europe now provides a general overview of the diversity of plants processed and of the techniques involved in their treatment prior to food preparation. The grinding of cereals has been shown to have predominated, but legumes, nuts and grass plants also played a major role. Nonetheless, depending on the region and cultural background, different types of grinding systems were employed, suggesting a strong link with varied food habits throughout the continent. After presenting an overview of our knowledge of plant transformation for food preparation, we look at challenging new issues for future research, most of which are centred on methodological improvements.